POPULASI BAKTERI ASAM LAKTAT PADA BUDIDAYA IKAN NILA YANG DIBERI PAKAN FERMENTASI LIMBAH PERTANIAN DENGAN SUPLEMEN ENCENG GONDOK DAN PROBIOTIK - Andhika Agus Setyawan; Sukanto Sukanto; Endang Widyastuti (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
The aim of this study were to determine the effect of fermented agricultural wastes feeding with supplement of water hyacinth and MEP+ probiotic towards the increasing population of intestinal Lactid Acid Bacteria (LAB) in Tilapia and to know the highest population of lactic acid bacteria after fermented agricultural waste feeding with water hyacinth supplements and MEP+ probiotic. Independent variable in this study was fermented feed with the addition of different water hyacinth and MEP+ probiotics. The experimental study was continued using completely randomized design (CRD). The dependent variable in this study was the number density of Lactobacillus bacteria in the gut of Tilapia. The main parameters measured were the number of LAB. Proponent parameters were namely Tilapia weight gain, physical and chemical conditions of the water. The results showed that feeding fermentative effected in increasing the population of lactic acid bacteria in the gut of Tilapia. Fermentative feed supplement agricultural waste with water hyacinth as much as 10% and MEP+ probiotic was the best treatment with LAB population density in Tilapia intestine with the average of 5.85 x 106 CFU /g.